Abóboda da capela Sistina: afrescos de Michelangelo - Carlini, Jade Hardt (2023)
This work aims to identify and highlight the frescoes made by Michelangelo in the vault of the Sistine Chapel. Throughout this monograph we will study the process of creation and execution of the frescoes, as well as the iconography existing there from historians and theorists such as Giorgio Vasari, Ernest Gombrich, Gilles Néret, Erwin Panofsky among others. It will also be glimpsed, in addition to the above, the history about the Sistine Chapel, Michelangelo and Popes Sixtus IV and Julius II – the latter two being responsible for the commissions for the Chapel. In addition, we will talk about the designs for the frescoes and briefly analyze the scene “Creation of Adam”. Therefore, this work will conclude by highlighting the historical importance of the Sistine Chapel.